Sosialisasi dan Pelatihan Publikasi Ilmiah pada Jurnal Nasional Terakreditasi Bagi Mahasiswa - Alsri Windra Doni; Nurul Aziza Ath Thaariq; Kori Kornelia; Aprizal Ponda; Evino Sugriarta (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
This community service activity aimed to enhance the ability of students at Poltekkes Kemenkes Padang to publish their research findings in nationally accredited journals. The main problem identified was the students’ limited understanding of article writing structure, publication ethics, and journal selection strategies. The implementation method applied the Asset Based Community Development (ABCD) approach through five stages—discovery, dream, design, define, and destiny—which involved observation, training design, socialization, and hands-on practice. The program was conducted through lectures, simulations, interactive discussions, and evaluation using pre- and post-tests involving 50 seventh-semester students. The results showed a significant improvement in students’ knowledge, with the average score increasing from 12.14 to 17.66 (p=0.000), and an increase of 25–45% in their understanding of scientific article writing. The outputs included published articles, an ISBN-registered guidebook, intellectual property rights (HKI), and video documentation. In conclusion, this training and socialization program effectively improved students’ literacy in scientific publication and contributed to strengthening the academic culture and publication reputation of Poltekkes Kemenkes Padang.